Bullying as Gendered Violence: Girls Talk of Their Classroom Experiences within a Heterogeneous Classroom - Okeke, Chinedu I.O. (EDUCARE, 2012)
ABSTRACT: Bullying is a global phenomenon with devastating consequences for the victims, their families, and the societies at large. Bullying is a serious social ill; a lived experience capable of turning individuals within a given society into social misfits with long-term implications. This paper reflects on the account of the stories by some Nigerian school girls of their classroom experiences in a heterogeneous school setting. Aspects of the deliberations from among the 25 girls (and 25 boys as well) who took part in the study are employed in this paper to interrogate how gendered bullying played into the girlsâ perceptions of their classroom. Results from the study show that within co-educational classroom, girls are more likely to be bully-victims than boys. Results also revealed that boys are more likely to be perpetrators of bullying than girls in a mixed-sex classroom. Bullying as lived experience, therefore, emerges in the study as a form of belligerent masculinity; and is germane to the understanding of the girl participantsâ submissive posture as they struggled for space and identity within the classroom in complex and subtle ways. The implications of this for co-education and co-educational policy-making are highlighted and recommendations for changes in policy and practice are equally suggested.Â Â Â  KEY WORDS: Schooling, classroom bullying, girlsâ participation, gender, Nigerian school girls, and co-education and co-educational policy-making.About the Author: Chinedu I.O. Okeke, Ph.D. is a Lecturer at the Department of Educational Foundations & Management, Faculty of Education UOS (University of Swaziland), Kwaluseni Campus, Private Bag 4 Kwaluseni M201, Swaziland, Africa. Phone: +26825170374. Fax: +26825185276. Email address: okekechinedu@yahoo.com and ciookeke@gmail.comHow to cite this article? Okeke, Chinedu I.O. (2012). âBullying as Gendered Violence: Girls Talk of Their Classroom Experiences within a Heterogeneous Classroomâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.1-14. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 15, 2012); Revised (July 17, 2012); and Published (August 17, 2012).